Copper alloy sheet and method for manufacturing the same, and electronic component and forged product

CN118019868BActive Publication Date: 2026-10-27FURUKAWA ELECTRIC CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202280065056.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-12-08
Filing Date
2022-12-05
Publication Date
2026-10-27
Estimated Expiration
2042-12-05

AI Technical Summary

Technical Problem

此外,当重视铜合金板材的机械特性时,难以加工成目标的难加工形状,因此难以满足针对电子机械等的小型化的要求

Benefits of technology

[0027]根据本发明,能够提供一种铜合金板材及其制造方法,所述铜合金板材具有高拉伸强度并且能够稳定地获得优异的锻敲加工性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118019868B_ABST
    Figure CN118019868B_ABST
Patent Text Reader

Abstract

Provided is a copper alloy sheet having high tensile strength and excellent forgeability, and a method for producing the same. The copper alloy sheet has an alloy composition containing one or both of Ni and Co in a range of 1.00 to 5.00 mass%, Si in a range of 0.20 to 1.50 mass%, and the balance being Cu and unavoidable impurities, and has a tensile strength of 550 MPa or more, and a grain area ratio of grains having a GAM value in a range of 0.1 to 0.8° or more, as obtained from crystal orientation analysis data by SEM-EBSD, in a range of 30% or more and 90% or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a copper alloy sheet and its manufacturing method, as well as electronic components and forged products. Background Technology

[0002] Copper alloy sheets are used in applications such as connectors, lead frames, relays, switches, sockets, shielding shells, shielding cans, camera module shells, heat dissipation parts for LCD and OLED (electroluminescent) displays, reinforcing plates, chassis, automotive connectors, shielding shells, and shielding cans. They are frequently subjected to pressure processing such as stamping, bending, forging, and bulging.

[0003] It is known that copper alloy sheets, in order to achieve shapes that would otherwise be difficult to machine through such pressure processing, must sacrifice mechanical properties. The term "difficult-to-machine shape" here refers to, for example, the shape formed when, during the manufacture of forged and hammered articles, a jig or punch with a smaller radius of curvature at the corners and edges than usual is used. Furthermore, "forged and hammered article" refers to an article formed by forging and hammering, characterized by the absence of joints in the formed article. Additionally, "forging and hammering" is a metal sheet forming method, typically referring to a process in which a punch is pressed into a thin sheet of metal to form a bottomed container of various shapes such as cylinders, cones, and angled tubes. Moreover, "forged and hammered article" also includes articles formed by combining forging and hammering with other processing methods different from forging and hammering, such as bending, crushing, and twisting.

[0004] When manufacturing forged parts with such difficult-to-machine shapes, it's difficult to say that the inherent mechanical properties of copper alloy sheets are fully utilized. Furthermore, when prioritizing the mechanical properties of copper alloy sheets, it's difficult to machine them into the desired difficult-to-machine shape, thus hindering the miniaturization requirements for electronic components and the like. One reason for this is that the radius of curvature of the jig (punch) must be increased to a certain extent, naturally increasing the mounting space for the forged parts used to construct electronic components. Moreover, while there is room to improve heat dissipation by optimizing the shape of the forged part, sacrificing only the aspects important for forging performance, it is often difficult to forge it into its optimal shape.

[0005] Regarding this point, Patent Document 1 discloses a Cu-Ni-Si copper alloy plate containing 1.0 to 3.0% by mass of Ni and Si at a concentration of 1 / 6 to 1 / 4 by mass of Ni, with the remainder consisting of Cu and unavoidable impurities. When the orientation of all pixels within the measurement area is determined using an EBSD method performed by a scanning electron microscope equipped with a backscattered electron diffraction imaging system at a step size of 0.5 μm, and boundaries with an orientation difference of 5° or more between adjacent pixels are considered grain boundaries, the average orientation difference between all pixels within the grain is 45% to 55% of the area of ​​grains with an orientation difference of less than 4°. The area average GAM of the grains present within the measurement area is 0.8 to 1.6°, and the number of Ni-Si precipitate particles with a particle size exceeding 100 nm is 0.2 to 0.7 particles / μm. 2 Furthermore, the concentration of Si dissolved within the grains is 0.1–0.4% by mass. Patent Document 1 suggests that controlling the average orientation difference within the grains and the grain size of the NiSi compound can improve the elastic properties of the copper alloy plate. Additionally, Patent Document 1 suggests that controlling the area average GAM value of the grains and the concentration of dissolved Si can improve the fatigue resistance of the copper alloy plate after bending processing.

[0006] Furthermore, Patent Document 2 discloses a Cu-Ni-Si copper alloy plate containing 1.0 to 3.0% by mass of Ni and Si at a concentration of 1 / 6 to 1 / 4 by mass of Ni, with the remainder consisting of Cu and unavoidable impurities. The surface has an arithmetic mean roughness (Ra) of 0.02 to 0.2 μm, and the standard deviation of the absolute values ​​of the individual peaks and valleys relative to the surface roughness mean line is 0.1 μm. Below μm, the average aspect ratio (minor axis of grain / major axis of grain) of the grains in the alloy microstructure is 0.4 to 0.6. When the orientation of all pixels within the measurement area is determined by the EBSD method using a scanning electron microscope with a backscattered electron diffraction imaging system, and the boundary with an orientation difference of 5° or more between adjacent pixels is considered as a grain boundary, the average GOS (grain orientation distribution) of the whole grains is 1.2 to 1.5°. The ratio of the total special grain boundary length Lσ to the total grain boundary length L of the grain boundary (Lσ / L) is 60 to 70%, and the elastic limit is 450 to 600 N / mm. 2 It is believed that the copper alloy plate in Patent Document 2, by setting the Lσ / L ratio to 60-70%, can improve the deep drawing processability.

[0007] [Previous Technical Documents]

[0008] (Patent Documents)

[0009] Patent Document 1: Japanese Patent Application Publication No. 2012-136726

[0010] Patent Document 2: International Publication No. 2012 / 160726 Summary of the Invention

[0011] [The problem the invention aims to solve]

[0012] With the miniaturization and thinning of electrical / electronic components and automotive parts in recent years, there is a growing demand for higher mechanical properties in the components used to construct these parts, namely press-processed products. In particular, connectors (connector housings and hold-down devices, etc.) and module housings (small camera module housings, shielding housings, battery module housings, etc.) manufactured by deep drawing processes and used in electronic devices are seeking a balance between higher tensile strength and forging properties.

[0013] In this regard, Patent Document 1 did not conduct any research on forging workability, and it did not disclose a good balance between high tensile strength and excellent forging workability, nor did it show the evaluation results of these properties.

[0014] Furthermore, in Patent Document 2, the ratio (Lσ / L) of the total special grain boundary length Lσ of the special grain boundary to the total grain boundary length L of the grain boundary is set within a predetermined range, which can improve the deep drawing processability. However, since the forging and hammering test was only conducted after relatively mild forging and hammering, it is expected to further improve the balance between high tensile strength and excellent forging and hammering processability.

[0015] Therefore, the present invention was developed in view of the above-mentioned problems, and aims to provide a copper alloy plate and a method for manufacturing the same, wherein the copper alloy plate has high tensile strength and can stably obtain excellent forging and hammering properties.

[0016] [Technical means to solve the problem]

[0017] The inventors have made the following discovery to complete the present invention: a copper alloy sheet having an alloy composition containing one or both of Ni and Co in the range of 1.00% by mass to 5.00% by mass, Si in the range of 0.20% by mass to 1.50% by mass, and the balance being composed of Cu and unavoidable impurities. In the copper alloy sheet, the tensile strength is set to be 550 MPa or more, and the area ratio of grains with GAM values ​​obtained from crystal orientation analysis data by SEM-EBSD method in the range of 0.1° to 0.8° is set to be 30% to 90%. This improves the tensile strength of the copper alloy sheet and enhances its workability, particularly the uniformity of the shape of forged products.

[0018] (1) A copper alloy plate having an alloy composition, said alloy composition containing one or both of Ni and Co in the range of 1.00% by mass and 5.00% by mass, Si in the range of 0.20% by mass and 1.50% by mass, and the balance being composed of Cu and unavoidable impurities, and having a tensile strength of 550 MPa or more, and the area ratio of grains with GAM values ​​obtained from crystal orientation analysis data by SEM-EBSD method in the range of 0.1° or more and 0.8° or less is in the range of 30% or more and 90% or less.

[0019] (2) The copper alloy sheet as described in (1) above has a work hardening index (n value) in the range of 0.10 or higher and 0.20 or lower.

[0020] (3) The copper alloy plate as described in (1) or (2) above, wherein the average grain size obtained from the crystal orientation analysis data by SEM-EBSD method is in the range of 4 μm or more and 25 μm or less, and the standard deviation of the aforementioned average grain size is 6 μm or less.

[0021] (4) The copper alloy sheet as described in any one of (1) to (3) above, wherein the aforementioned alloy composition further contains at least one arbitrary additive ingredient selected from the group consisting of Zn, Sn, Mg, Cr and Fe, in an aggregate range of more than 0.10% by mass and less than 1.00% by mass.

[0022] (5) An electronic component formed using any one of the copper alloy sheets described in (1) to (4) above.

[0023] (6) A forged product obtained by forging a copper alloy sheet as described in any one of (1) to (4) above.

[0024] (7) A method for manufacturing a copper alloy sheet, comprising the method for manufacturing a copper alloy sheet as described in any one of (1) to (4) above, wherein a copper alloy material having an alloy composition equivalent to the aforementioned alloy composition is subjected to a melting and casting step [step 1], a reheating step [step 2], a hot rolling step [step 3], a first cold rolling step [step 4], a first annealing step [step 5], a second cold rolling step [step 6], a second annealing step [step 7], a third annealing step [step 8], a third cold rolling step [step 9], and a fourth annealing step [step 10], wherein in the aforementioned first annealing step... In step [5], the reaching temperature is set to a range of 800°C or higher and 1000°C or lower, and the holding time is set to a range of 5 seconds or higher and 30 seconds or lower. In the aforementioned second cold calendering step [6], the product of the processing rate [%] per operation and the calendering roll diameter [mm] is set to 2000% [mm] or lower. In the aforementioned third cold calendering step [9], the total processing rate is set to a range of 1% or higher and 10% or lower. In the aforementioned fourth annealing step

[10] , the reaching temperature (T) is set to a range of 400°C or higher and 600°C or lower, while applying tension (F (kgf / mm)). 2 While annealing is being performed, the tension satisfies the inequality expressed by equation (I) in relation to the aforementioned reached temperature (T(°C)).

[0025] −0.0015×T+1.20≤F≤−0.0015×T+1.80 Formula (I).

[0026] [effect]

[0027] According to the present invention, a copper alloy sheet and a method for manufacturing the same are provided, wherein the copper alloy sheet has high tensile strength and can be stably and effectively forged. Attached Figure Description

[0028] Figure 1 This diagram illustrates the concept of pressing the central portion of a test sheet W into a punch with a cylindrical front end and a small radius of curvature R at the corners using a deep drawing tester to evaluate forging workability. Detailed Implementation

[0029] Next, embodiments of the present invention will be described. The following description is merely an example illustrating embodiments of the present invention and is not intended to limit the scope of the patent application.

[0030] The copper alloy plate of the present invention has an alloy composition containing one or both of Ni and Co in the range of 1.00% by mass and 5.00% by mass, Si in the range of 0.20% by mass and 1.50% by mass, and the balance being composed of Cu and unavoidable impurities. Furthermore, the tensile strength is 550 MPa or more, and the area ratio of grains with GAM values ​​obtained from crystal orientation analysis data by SEM-EBSD method in the range of 0.1° or more and 0.8° or less is 30% or more and 90% or less.

[0031] The copper alloy sheet of the present invention, manufactured under appropriate manufacturing conditions with one or both of Ni and Co and Si in appropriate amounts, can improve the tensile strength, particularly the tensile strength, of the copper alloy sheet while reducing the variation in grain size caused by residual Si compounds. Furthermore, by setting the area ratio of grains with GAM values ​​in the range of 0.1° to 0.8° obtained from SEM-EBSD crystal orientation analysis data to be 30% to 90%, the tensile strength of the copper alloy sheet can be improved, as well as its workability, particularly the uniformity of the shape of forged articles. Therefore, the copper alloy sheet of the present invention provides a copper alloy sheet and a method for manufacturing the same, which exhibits high tensile strength and consistently excellent workability.

[0032] [1] Alloy composition of copper alloy plates

[0033] The copper alloy sheet of the present invention contains one or both of Ni and Co in a range of 1.00% by mass and 5.00% by mass, and Si in a range of 0.20% by mass and 1.50% by mass as essential components.

[0034] The following explains the reasons for limiting the alloy composition of copper alloy plates.

[0035] (Ni and Co: totaling more than 1.00% by mass and less than 5.00% by mass)

[0036] Both Ni (nickel) and Co (cobalt) are important components that improve the tensile strength of copper alloy sheets. From the viewpoint of achieving this effect, it is necessary to add one or both of Ni and Co, with a combined content in the range of 1.00% by mass or more and 5.00% by mass or less. Here, if the combined amount of Ni and Co exceeds 5.00% by mass, Si compounds will remain in the first annealing step [step 5] described later, and the variation in grain size is likely to increase. Therefore, the combined amount of Ni and Co is preferably set to a range of 1.50% by mass or more and 4.00% by mass or less.

[0037] (Si: ≥0.20% by mass and ≤1.50% by mass)

[0038] Silicon (Si) is an important component that improves the tensile strength of copper alloy sheets. From the viewpoint of achieving this effect, the Si content needs to be set at 0.20% by mass or higher. On the other hand, if the Si content exceeds 1.50% by mass, the conductivity decreases significantly, and the variation in grain size increases; therefore, the upper limit of the Si content needs to be set at 1.50% by mass.

[0039] <Add any ingredients>

[0040] Furthermore, the copper alloy sheet of the present invention may further contain at least one arbitrary additive component selected from the group consisting of Zn, Sn, Mg, Cr and Fe, in a total range of 0.10% by mass or more and 1.00% by mass or less.

[0041] (Zn: ≥0.10% by mass and ≤0.50% by mass)

[0042] Zinc (Zn) is a component that improves the adhesion and migration properties of Sn plating. For this effect to be achieved, it is preferable to set the Zn content to 0.10% by mass or more. On the other hand, if the Zn content exceeds 0.50% by mass, there is a tendency for decreased conductivity. Therefore, the Zn content is preferably in the range of 0.10% by mass or more and 0.50% by mass or less.

[0043] (Sn: ≥0.10% by mass and ≤0.30% by mass)

[0044] Sn (tin) is a component that improves stress-relieving properties. For this effect to occur, the Sn content is preferably 0.10% by mass or more. On the other hand, if the Sn content exceeds 0.30% by mass, there is a tendency for decreased conductivity. Therefore, the Sn content is preferably in the range of 0.10% by mass or more and 0.30% by mass or less.

[0045] (Mg: ≥0.10% by mass and ≤0.30% by mass)

[0046] Magnesium (Mg) is a component that improves stress-relieving properties. For this effect to be achieved, it is preferable to set the Mg content to 0.10% by mass or more. On the other hand, if the Mg content exceeds 0.30% by mass, there is a tendency for decreased electrical conductivity. Therefore, the Mg content is preferably in the range of 0.10% by mass or more and 0.30% by mass or less.

[0047] (Cr: ≥0.05% by mass and ≤0.30% by mass)

[0048] Chromium (Cr) is a component that inhibits grain coarsening during melt heat treatment. For this effect to be effective, a Cr content of 0.05% by mass or more is preferred. Furthermore, if the Cr content exceeds 0.30% by mass, coarse Cr-containing crystals are easily formed during casting, which can easily become the initiation point for cracking. Therefore, the Cr content is preferably in the range of 0.05% by mass or more and 0.30% by mass or less.

[0049] (Fe: ≥0.05% by mass and ≤0.30% by mass)

[0050] Iron (Fe) is a component that helps suppress grain coarsening during melt heat treatment. For this effect to be effective, it is preferable to set the Fe content to 0.05% by mass or more. Furthermore, if the Fe content exceeds 0.30% by mass, coarse Fe-containing crystals are easily formed during casting, which can easily become the initiation point for cracking. Therefore, the Fe content is preferably in the range of 0.05% by mass or more and 0.30% by mass or less.

[0051] (Total content of any added ingredients: ≥0.10% by mass and ≤1.00% by mass)

[0052] To achieve the aforementioned effects from the optional added ingredients, these optional added ingredients are preferably present in a total of 0.10% by mass or more. On the other hand, if these optional added ingredients are present in large quantities, they are prone to forming compounds with the necessary ingredients; therefore, it is preferable that their total content is 1.00% by mass or less.

[0053] (Remaining components: Cu and unavoidable impurities)

[0054] The Cu alloy used to construct the copper alloy sheet has an alloy composition, wherein, in addition to the components mentioned above, the remaining portion consists of Cu (copper) and unavoidable impurities. Furthermore, the term "unavoidable impurities" refers to impurities that are generally present in the raw materials of the metal product, or that are unavoidably introduced during the manufacturing process and are not originally desired, but are permissible because they are present in trace amounts and do not affect the properties of the metal product. Examples of unavoidable impurities include non-metallic elements such as sulfur (S), carbon (C), and oxygen (O); and metallic elements such as antimony (Sb). Furthermore, the upper limit of the content of these components can be set, for example, 0.05% by mass for each of the above components, and 0.20% by mass for the total amount of the above components.

[0055] Tensile strength of copper alloy sheet

[0056] The copper alloy sheet of the present invention requires a tensile strength of 550 MPa or higher when stretched in a direction parallel to the rolling direction. This allows the copper alloy sheet to achieve the desired tensile strength even when used for small and thin parts such as electrical / electronic components and automotive parts, thus enabling its suitable use in these applications. Here, the tensile strength is measured using two test pieces of JIS Z2241 No. 13B, and the average tensile strength obtained from the two test pieces is taken as the measured value of the tensile strength. These test pieces are cut such that the direction parallel to the rolling direction is the long side direction.

[0057] [3] GAM value and area ratio of copper alloy plates

[0058] The GAM (grain average misorientation) value is obtained from crystal orientation analysis data by SEM-EBSD method, and is obtained in the following way: within grains with large-angle grain boundaries with an azimuth difference of more than 15°, the distance between measurement points (hereinafter also referred to as step size) is measured at 0.5 μm, and the azimuth difference of each adjacent measurement point is calculated. Then, the average value of the calculated azimuth difference is calculated within the same grain.

[0059] When the GAM value is small, the average orientation difference within a grain decreases, resulting in uniform grains with less strain or grains with continuous orientation gradients. On the other hand, when the GAM value is large, the average orientation difference within a grain increases, thus increasing the local strain within a grain.

[0060] In the copper alloy sheet of the present invention, the area proportion of grains with GAM values ​​ranging from 0.1° to 0.8° is between 30% and 90% in the crystal orientation analysis data obtained by SEM-EBSD. This improves the tensile strength of the copper alloy sheet and enhances the shape uniformity of forged articles. Specifically, setting this area proportion to 30% or more increases the proportion of grains with small orientation differences within the copper alloy sheet, resulting in stable grain orientation and thus improving the workability of the copper alloy sheet, particularly the shape uniformity of forged articles. Conversely, setting this area proportion to 90% or less suppresses the reduction in tensile strength of the copper alloy sheet.

[0061] Here, the GAM value is obtained from the crystal orientation data continuously measured using the EBSD detector included in a high-resolution scanning analytical electron microscope (JEOL Ltd., JSM-7001FA), and calculated using analysis software (TSL Corporation, OIM Analysis). Furthermore, "EBSD" stands for Electron Backscattered Electron Diffraction, a crystal orientation resolution technique that utilizes the reflected electron Kikuchi lines diffracted by an electron beam irradiating a sample (copper plate) within a scanning electron microscope (SEM). "OIM Analysis" refers to the analysis software for the data obtained using EBSD. Measurements are performed in 0.5 μm increments within a field of view of approximately 400 μm × 800 μm. Measurements can be performed on a cross-section along the rolling direction of a copper alloy plate after it has been impregnated with resin and finished with mechanical grinding and polishing (colloidal silica). In addition, measurements can also be performed on the surface of copper alloy plates after electrolytic polishing. The measurement area in their cross-section and surface is set to approximately 400 μm × 800 μm. When the above-mentioned field of view size cannot be obtained by means of the sample size when measuring both the cross-section and surface, the value obtained by averaging the measurements from multiple fields of view can also be used. The analysis of GAM values ​​defines the grain boundary as having an orientation difference of 15° or more, and the measurement points containing the reliability index CI value of 0.1 or more within the grain boundary are set as the objects of analysis.

[0062] [4] Average grain size and standard deviation of copper alloy plates

[0063] The preferred embodiment of the copper alloy plate of the present invention is that the average grain size obtained from the crystal orientation analysis data by SEM-EBSD method is in the range of 4 μm or more and 25 μm or less, and the standard deviation of the average grain size is 6 μm or less. Here, the analysis of the average grain size is defined as the grain boundary having an orientation difference of 15° or more, and grains with a size of 2 pixels or more are set as the objects of analysis.

[0064] In particular, setting the average grain size to 4 μm or more further improves the forging and hammering properties of copper alloy sheets. On the other hand, if the average grain size is greater than 25 μm, there is a possibility that ridging may form, impairing the appearance of the forged and hammered workpiece. Therefore, the average grain size of copper alloy sheets is preferably in the range of 4 μm or more and 25 μm or less.

[0065] Furthermore, by setting the standard deviation of the average grain size to below 6 μm, the variation in grain size of the copper alloy sheet is reduced, making it less prone to stress concentration during forging and hammering, thus further improving the forging and hammering properties of the copper alloy sheet.

[0066] The average grain size and standard deviation of the copper alloy plate can be set as the weighted average and standard deviation of the diameters of more than 500 grains randomly selected from the crystal orientation analysis data obtained by the SEM-EBSD method described above.

[0067] [5] Work hardening index (n value) of copper alloy sheet

[0068] The copper alloy sheet of the present invention preferably has a work hardening index (n value) in the range of 0.10 or higher and 0.20 or lower. Setting the work hardening index within this range allows for higher tensile strength of the copper alloy sheet without compromising its workability. On the other hand, if the work hardening index is lower than 0.10, the workability of the copper alloy sheet tends to decrease.

[0069] The work hardening index (n-value) can be determined using the test methods specified in JIS Z2253:2011. For example, the work hardening index (n-value) can be calculated from data in the range of true strain between 2% and 8%.

[0070] [6] An example of a method for manufacturing copper alloy plates

[0071] The aforementioned copper alloy sheet can be achieved by combining and controlling the alloy composition and the manufacturing process, which is not particularly limited. One example of a process that achieves such high tensile strength and consistently excellent forging workability is the following method.

[0072] An example of the method for manufacturing the copper alloy sheet of the present invention is as follows: A copper alloy material having an alloy composition identical to that of the copper alloy sheet described above is subjected to at least the following steps in sequence: melting and casting [Step 1], reheating [Step 2], hot rolling [Step 3], first cold rolling [Step 4], first annealing [Step 5], second cold rolling [Step 6], second annealing [Step 7], third annealing [Step 8], third cold rolling [Step 9], and fourth annealing [Step 10]. In the first annealing step [Step 5], the reaching temperature is set to a range of 800°C or higher and 1000°C or lower, and the holding time is set to a range of 5 seconds or higher and 30 seconds or lower. Furthermore, in the second cold rolling step [Step 6], the product of the processing rate [%] per operation and the rolling roll diameter [mm] is set to 2000 [%·mm] or lower. Furthermore, in the third cold rolling step [Step 9], the total processing rate is set to a range of 1% or more and 10% or less. Furthermore, in the fourth annealing step [Step 10], the reaching temperature (T) is set to a range of 400°C or more and 600°C or less, while a tension (F (kgf / mm)) is applied. 2 While annealing is being performed, the tension, expressed as a relationship with the reached temperature (T(°C)), satisfies the inequality expressed by equation (I).

[0073] −0.0015×T+1.20≤F≤−0.0015×T+1.80 Formula (I).

[0074] (i) Melting and casting steps [Step 1]

[0075] The melting and casting step [Step 1] involves melting and casting a copper alloy material having an alloy composition identical to the aforementioned alloy composition to produce an ingot (e.g., 30 mm thick, 100 mm wide, and 150 mm long) of a predetermined shape. Preferably, the melting and casting step [Step 1] uses a high-frequency melting furnace to melt and cast the copper alloy material in an atmosphere, an inert gas environment, or a vacuum. Furthermore, while the alloy composition of the copper alloy material may vary depending on the added components during the various manufacturing steps, it may sometimes adhere to the melting furnace or volatilize, and may not be completely identical to the alloy composition of the manufactured copper alloy sheet, but it will have an alloy composition substantially the same as that of the copper alloy sheet.

[0076] (ii) Reheating step [Step 2]

[0077] The reheating step [Step 2] is a heat treatment step performed on the ingot after the casting step [Step 1]. The conditions for the heat treatment in the reheating step [Step 2] are as usual and are not particularly limited. An example of the heat treatment conditions here is a temperature range of 850°C to 1000°C and a holding time of 1 hour to 5 hours.

[0078] (iii) Hot rolling step [Step 3]

[0079] The hot rolling step [Step 3] is a step of producing hot-rolled material by hot rolling the ingot after the reheating step [Step 2] until it reaches a predetermined thickness. In the hot rolling step [Step 3], it is preferable, for example, to set the rolling temperature to 700°C or higher and the total reduction rate to 50% or higher.

[0080] Here, "processing rate" (reduction rate) is the value obtained by subtracting the cross-sectional area after calendering from the cross-sectional area before calendering, dividing it by the cross-sectional area before calendering, multiplying it by 100, and expressing it as a percentage, as shown in the following formula.

[0081] [Processing rate] = {([Sectional area before rolling] - [Sectional area after rolling]) / [Sectional area before rolling]} × 100 (%)

[0082] The hot-rolled material after the hot rolling step [step 3] is preferably cooled. Here, there is no particular limitation on the means of cooling the hot-rolled material. For example, from the viewpoint of making it less likely for grain coarsening to occur, it is preferable to increase the cooling rate as much as possible. It is preferable to set the cooling rate to 10°C / second or more by means such as water cooling.

[0083] Here, the cooled hot-rolled material can be subjected to planar cutting to remove surface defects. Planar cutting removes the oxide film and defects generated in the hot working step [Step 3]. The conditions for planar cutting are not particularly limited and can be any normally performed conditions. The amount removed from the surface of the hot-rolled material by planar cutting can be adjusted appropriately according to the conditions of the hot working step [Step 3], and can be set to, for example, approximately 0.5 mm to 4 mm.

[0084] (iv) First cold rolling step [Step 4]

[0085] The first cold rolling step [Step 4] is a step of cold rolling the hot-rolled material after the hot-processing step [Step 3]. The rolling in the first cold rolling step [Step 4] can be performed with any reduction rate according to the thickness of the product sheet, for example, the total processing rate can be set to a range of 50% or more and 90% or less.

[0086] (v) First annealing step [Step 5]

[0087] The first annealing step [step 5] is a step of heat treatment performed on the cold-rolled material after the first cold rolling step [step 4] according to the alloy composition.

[0088] The annealing conditions in the first annealing step [Step 5] are such that by setting the temperature to a range of 800°C or higher and 1000°C or lower, and the holding time to a range of 5 seconds or higher and 30 seconds or lower, the Si compound can be dissolved, resulting in a uniform distribution of undissolved Si compound and improved grain uniformity during recrystallization. If the temperature is below 800°C or the holding time is below 5 seconds, there is a tendency for uneven distribution of undissolved Si compound and reduced grain uniformity during recrystallization. On the other hand, if the temperature exceeds 1000°C or the holding time exceeds 30 seconds, problems such as grain coarsening and abnormal grain growth will occur, leading to variations in properties, which is undesirable.

[0089] (vi) Second cold rolling step [Step 6]

[0090] The second cold rolling step [Step 6] is a step of further cold rolling the cold-rolled material after the first annealing step [Step 5] using a work roll. In the second cold rolling step [Step 6], the product of the processing rate [%] per operation and the diameter of the work roll (rolling roll diameter) [mm] is set to 2000 [%·mm] or less. If this product is greater than 2000 [%·mm], shear deformation is likely to occur only on the surface of the copper alloy sheet, resulting in differences in deformation amount and crystal orientation between the sheet and the interior. Therefore, when recrystallizing it through subsequent heat treatment, the uniformity of grain size is reduced. Therefore, the product of the processing rate [%] per operation and the rolling roll diameter [mm] in the second cold rolling step [Step 6] is preferably 1600 [%·mm] or less, and more preferably 1000 [%·mm] or less.

[0091] Furthermore, the diameter of the calendering rolls used in the second cold calendering step [step 6] can be set to a range of 60 mm or more and 400 mm or less. Furthermore, the processing rate [%] for each operation in the second cold calendering step [step 6] can be set to a range of 5% or more and 50% or less. Furthermore, the total processing rate in the second cold calendering step [step 6] can be set to a range of 5% or more and 70% or less.

[0092] (vii) Second annealing step [Step 7]

[0093] The second annealing step [Step 7] is an annealing step that involves heat treatment of the cold-rolled material after the second cold rolling step [Step 6] to induce recrystallization. Here, the heat treatment conditions in the second annealing step [Step 7] can be set, for example, to a temperature range of 800°C or higher and 1000°C or lower, and a holding time at that temperature range of 5 seconds or higher and 30 seconds or lower. Here, when the temperature exceeds 1000°C and the holding time exceeds 30 seconds, the grains tend to coarsen. Furthermore, when the holding time exceeds 30 seconds, the grain size tends to vary, and the standard deviation of the average grain size increases, thus causing stress concentration during forging and easily leading to reduced machinability. Additionally, when the temperature reaches less than 800°C and the holding time is less than 5 seconds, the solid solution content decreases, and the precipitation strengthening amount decreases.

[0094] The cold-rolled material after the second annealing step [step 7] is preferably cooled immediately. Here, there is no particular limitation on the means of cooling the hot-rolled material. For example, from the viewpoint that it is not easy to cause a decrease in tensile strength due to grain coarsening, it is preferable to increase the cooling rate as much as possible. It is preferable to set the cooling rate to 50°C / second or more by means such as water cooling.

[0095] (vii) Third annealing step [Step 8]

[0096] The third annealing step [Step 8] is an annealing step that performs heat treatment on the cooled, cold-drawn material to cause it to recrystallize. Here, the conditions for heat treatment in the third annealing step [Step 8] are: a temperature reaching 450°C or higher and 600°C or lower, and a holding time at that temperature of 1 hour or higher and 5 hours or lower. Here, when the temperature reaches less than 450°C and the holding time is less than 1 hour, precipitation strengthening is difficult to achieve.

[0097] (ix) Third cold rolling step [Step 9]

[0098] The third cold rolling step [Step 9] is a step of further cold rolling the cold-rolled material after the third annealing step [Step 8]. The total processing rate in the third cold rolling step [Step 9] is set to a range of 1% or more and 10% or less. Here, when the total processing rate is less than 1%, the effect of improving the tensile strength of the copper alloy sheet will be reduced. In addition, when the total processing rate is greater than 10%, the forgeability of the copper alloy sheet will be reduced.

[0099] (x) Fourth annealing step [Step 10]

[0100] The fourth annealing step [Step 10] is an annealing step that adjusts the mechanical properties of the sheet material by means of displacement stabilization and recovery, after heat treatment of the cold-rolled material following the third cold rolling step [Step 9]. Here, the heat treatment conditions in the fourth annealing step [Step 10] are: setting the reaching temperature (T) to a range of 400°C or higher and 600°C, while applying a tension (F (kgf / mm²)). 2 While annealing, the tension, expressed as a relationship with the reached temperature (T (°C)), satisfies the inequality represented by equation (I). Furthermore, the holding time at the reached temperature (T) is preferably in the range of 5 seconds to 30 seconds.

[0101] −0.0015×T+1.20≤F≤−0.0015×T+1.80 Formula (I)

[0102] Applying tension (F) to the cold-rolled material in a manner that satisfies this inequality relationship can improve the balance between tensile strength, electrical conductivity, and workability of the resulting copper alloy sheet. In particular, annealing while applying tension (F) to the cold-rolled material makes it easier to reduce the residual strain in the copper alloy sheet even with low tension, thus improving the workability of the copper alloy sheet. Here, when the tension and the temperature and time of the heat treatment are insufficient, the residual strain in the copper alloy sheet increases, and the variation in the orientation of the grains contained in the copper alloy sheet increases, thus increasing the GAM value of the copper alloy sheet, resulting in decreased workability. In addition, the increase in residual strain in the copper alloy sheet and the decrease in the work hardening index of the copper alloy sheet also reduce the workability of the copper alloy sheet. Furthermore, if the tension and the temperature and time of the heat treatment are excessive, the tensile strength decreases, and the effect obtained by the second cold rolling step [step 6] is lost.

[0103] [7] Applications of copper alloy plates

[0104] The copper alloy sheet of the present invention is particularly suitable for forging to obtain forged products, and is suitable for forming, for example, electrical / electronic components and automotive parts. More specifically, it is particularly suitable for applications requiring miniaturization and thinning, such as connectors, lead frames, relays, switches, sockets, shielding shells, shielding cans, camera module shells, heat dissipation components for liquid crystal and organic EL displays, reinforcing plates, chassis, and automotive connectors, shielding shells, and shielding cans.

[0105] The above describes the embodiments of the present invention, but the present invention is not limited to the above embodiments, and includes all the forms included in the concept of the present invention and the scope of the claims, and various changes can be made within the scope of the present invention.

[0106] [Example]

[0107] Secondly, examples and comparative examples of the present invention are described in order to make the effects of the present invention clearer, but the present invention is not limited to these examples.

[0108] (Examples 1-32 of this invention and Comparative Examples 1-12)

[0109] After melting various copper alloy materials with the alloy compositions shown in Table 1, a melting casting step [Step 1] is performed, in which the materials are cooled in an atmospheric environment and cast to obtain an ingot. This ingot is then subjected to a reheating step [Step 2] for heat treatment at a temperature between 900°C and 1000°C and a holding time between 1 hour and 2 hours. Immediately afterwards, a hot rolling step [Step 3] is performed to roll the ingot so that the long side direction is aligned with the rolling direction, achieving a total processing rate of 50% or more, to obtain a hot-rolled material. This material is then cooled to room temperature by water cooling.

[0110] After the hot-rolled material has cooled, a first cold rolling step is performed [Step 4], in which the long side direction of the hot-rolled material is made to be the rolling direction under the condition that the total processing rate is above 80% and below 99%.

[0111] For the calendered material after the first cold calendering step [Step 4], a first annealing step [Step 5] is performed to heat treat the material at the temperature reached and the holding time as shown in Table 2. Then, a second cold calendering step [Step 6] is performed with a total processing rate of 5% to 70% to make the long side direction of the calendered material the calendering direction, under the conditions of the processing rate [%] of each operation, the diameter of the calendering roll (calendering roll diameter) [mm], and the product of the processing rate of each operation and the calendering roll diameter [%·mm] as shown in Table 2.

[0112] After the calendered material undergoes the second cold calendering step [Step 6], it undergoes a second annealing step [Step 7] to heat-treat the material at a temperature ranging from 800°C to 1000°C and a holding time ranging from 10 seconds to 30 seconds, and is immediately cooled to room temperature by water cooling.

[0113] For the cooled calendered material, a third annealing step [Step 8] is performed, which involves heat treatment at a temperature between 450°C and 550°C and a holding time of 2 hours. Then, a third cold rolling step [Step 9] is performed, in which the long side direction is oriented as the rolling direction, under the conditions of the total processing rate listed in Table 2. Here, for Comparative Example 4, the fourth annealing step [Step 10] described later is performed without the third cold rolling step [Step 9].

[0114] The rolled material after the third cold rolling step [step 9] is subjected to a fourth annealing step [step 10] to heat-treat the material by applying tension (F) while holding it for a period of 5 seconds to 30 seconds at the temperature set in Table 2, thereby producing the copper alloy sheet of the present invention. Here, the tension (F) applied to the rolled material is applied in a manner that is within the range of the inequality expressed by formula (I) as shown in Table 2.

[0115] In addition, in Table 1, components other than copper (Cu), Ni (nickel), Co (cobalt), and Si (silicon) are listed as optional additives. Furthermore, in Table 1, a horizontal line “-” is drawn in the column for components not present in the alloy composition of the copper alloy material, making it clearer that the corresponding component is not present or, even if present, is below the detection limit.

[0116] [Various Measurement and Evaluation Methods]

[0117] The copper alloy plates of the above-described examples and comparative examples of the present invention were used to evaluate the properties shown below. The evaluation conditions for each property are as follows.

[0118] [1] Determination of tensile strength of copper alloy sheet

[0119] Tensile strength was determined using two test pieces of No. 13B as specified in JIS Z2241, and the average tensile strength obtained from the two test pieces was taken as the measured value. The test pieces were cut from the test material with the long side parallel to the calendering direction as the long side direction. In this embodiment, a tensile strength of 550 MPa or higher was considered acceptable. The results are shown in Table 3.

[0120] [2] GAM value and area ratio of copper alloy plates

[0121] The GAM value of the copper alloy sheet was obtained from the crystal orientation data continuously measured using the EBSD detector attached to a high-resolution scanning analytical electron microscope (JEOL Ltd., JSM-7001FA) and calculated using analysis software (TSL Ltd., OIM Analysis). Measurements were performed in increments of 0.5 μm within a field of view of approximately 400 μm × 800 μm. Furthermore, the measurement was performed on a cross-section along the rolling direction after the copper alloy sheet was filled with resin and finished with mechanical grinding and polishing (colloidal silica). Grain boundaries were defined as having an orientation difference of 15° or more, and measurement points with a reliability index (CI) value of 0.1 or more within the grain boundaries were selected as the measurement targets. The area of ​​grains with GAM values ​​between 0.1° and 0.8° obtained in the above manner was calculated as the proportion of the area of ​​the measurement target, i.e., the entire area of ​​the SEM image. In addition, in this embodiment, the area ratio of grains with GAM values ​​between 0.1° and 0.8° that are 30% to 90% is defined as a qualified level. The results are shown in Table 3.

[0122] [3] Average grain size and standard deviation of copper alloy plates

[0123] The average grain size and standard deviation of the copper alloy sheet were obtained by calculating the weighted average and standard deviation of the diameters of more than 500 grains randomly selected from the crystal orientation analysis data obtained by the SEM-EBSD method described above. Here, the analysis of the average grain size defines the grain boundary as having an orientation difference of more than 15°, and grains with a size of more than 2 pixels are selected as the analysis objects. The results are shown in Table 3.

[0124] [4] Determination of the work hardening index (n value) of copper alloy plates

[0125] The work hardening index (n-value) of copper alloy sheet is determined by the test method specified in JIS Z2253:2011. In particular, in the examples and comparative examples of the present invention, the work hardening index (n-value) is calculated from data in the range of true strain being 2% or more and 8% or less.

[0126] [5] Evaluation of the forgeability of copper alloy sheets

[0127] The forging and hammering properties of copper alloy sheets are like Figure 1As shown, using a deep drawing tester (e.g., a sheet metal forming tester manufactured by ERICHSEN) 10, after the edge of the test sheet W is secured between the mold 12 and the anti-wrinkle member 16, the central part of the test sheet W is gradually pressed in with a punch 14 whose front end is cylindrical and whose corner radius of curvature R is small, thus forming a cylindrical cup body. At this time, the following results are evaluated according to the following evaluation criteria: the result of the minimum value of the corner radius of curvature R of the front end of the punch 14 that does not produce cracks; and the result of the absolute value of the slope of the linear approximation (variation of undulation) of the relationship between the angle (°) and the undulation height (μm) of the edge of the forged product after forging with the smallest punch diameter that does not produce cracks, measured at 45° intervals along the circumference from the rolling direction. Here, the thickness of the test plate W was set to 0.15 mm, the diameter of the test plate W was set to 61 mm, the diameter of the punch 14 was set to 33 mm, and the radius of curvature R of the corner of the front end of the punch 14 was set to six different values: 0.30 mm, 0.50 mm, 0.75 mm, 0.90 mm, and 1.00 mm. The gap between the punch 14 and the die 12 was set to 0.35 mm, and the radius of curvature of the shoulder of the punch 12 was set to 1.0 mm. Lubricating oil (trade name: PRETON R-303P, manufactured by SUGIMURAChemical Industrial Co., Ltd.) was applied to the surface of the punch 14 side of the test plate W. The results are shown in Table 3. In addition, for examples where the tensile strength was insufficient (examples where the tensile strength did not reach 550 MPa), the forging workability was not evaluated. Furthermore, for examples where the minimum value of the radius of curvature R at the corner of the front end of the punch 14 is evaluated as "×", the undulation height of the edge of the forged workpiece was not evaluated.

[0128] (a) Evaluation criteria for the minimum radius of curvature R of the corner at the front end of punch 14

[0129] ◎(Excellent): When the minimum value of the radius of curvature R is less than 0.5 mm

[0130] ○ (Good): When the minimum value of the radius of curvature R is greater than 0.5 mm and less than 0.75 mm

[0131] × (Not allowed): When the minimum value of the radius of curvature R exceeds 0.75 mm

[0132] (b) Evaluation criteria for the undulation of the edges of forged products

[0133] ◎(Excellent): When the variation in fluctuation is less than 0.5 mm

[0134] ○ (Good): When the variation in fluctuation is greater than 0.5 mm but less than 0.7 mm

[0135] △ (Allowed): When the variation in fluctuation is greater than 0.7 mm and less than 1.0 mm

[0136] × (Not allowed): When the variation in undulation exceeds 1.0 mm

[0137] <Comprehensive Assessment of Forging and Workability>

[0138] ◎ (Excellent): When both assessments in (a) and (b) above are marked with "◎"

[0139] ○ (Good): When both assessments in (a) and (b) above are marked with "◎", "○" or "△".

[0140] × (Not allowed): When at least one of the assessments in (a) and (b) above is marked "×".

[0141] [Table 1]

[0142]

[0143] [Table 2]

[0144]

[0145] [Table 3]

[0146]

[0147] As can be seen from the results in Tables 1 to 3, the alloy composition of the copper alloy plates of Examples 1 to 32 of the present invention is within the appropriate and correct range of the present invention, and the tensile strength is 550 MPa or more, and the area ratio of grains with GAM values ​​obtained from crystal orientation analysis data by SEM-EBSD method is in the range of 0.1° or more and 0.8° or less, is in the range of 30% or more and 90% or less. In this case, the forging workability is evaluated as "◎" or "○".

[0148] Therefore, the copper alloy plates of Examples 1 to 32 of the present invention have high tensile strength and can stably obtain excellent forging and hammering properties.

[0149] In particular, the product of the processing rate and the rolling roll diameter in the second cold rolling step [step 6] of the copper alloy sheet of Example 4 of the present invention is small, and it is not easily affected by surface shearing. We believe that the grain size after recrystallization is uniform, and the variation of fluctuations obtained in the evaluation of forging workability is also small.

[0150] Furthermore, the total processing rate of the third cold rolling step [step 9] of the copper alloy sheet of Example 9 of the present invention is small, or the tension applied to the cold-rolled material in the fourth annealing step [step 10] is small, and we believe that the balance between tensile strength and forging formability is excellent.

[0151] Furthermore, the copper alloy plates of Examples 13-15 of the present invention have a high total amount of Ni and Co, and the total processing rate of the third cold rolling step [step 9] is small, or the tension applied to the cold-rolled material in the fourth annealing step [step 10] is small. We believe that the balance between tensile strength and forging formability is excellent.

[0152] Furthermore, the total processing rate of the third cold rolling step [step 9] of the copper alloy sheet of Example 16 of the present invention is small, or the tension applied to the cold-rolled material in the fourth annealing step [step 10] is small, and we believe that the balance between tensile strength and forging formability is excellent. Also, the product of the processing rate per operation and the rolling roll diameter in the second cold rolling step [step 6] of the copper alloy sheet of Example 16 of the present invention is small, and we believe that the variation in fluctuations obtained in the evaluation of forging workability is small.

[0153] Furthermore, the product of the processing rate and the rolling roll diameter in each operation of the second cold rolling step [step 6] of the copper alloy sheet of Example 18 of the present invention is small, or the tension applied to the cold-rolled material in the fourth annealing step [step 10] is small, and we believe that the evaluation results of the forging formability and variability of the undulation are excellent.

[0154] On the other hand, the copper alloy plates of Comparative Examples 1 to 12 were all outside the proper scope of the present invention because at least one of the following factors—alloy composition, tensile strength, and grain area ratio in the range of 0.1° to 0.8°—was outside the appropriate scope of the present invention. Therefore, the tensile strength did not meet the acceptable level, or the comprehensive evaluation of forging workability was rated as "×".

[0155] Figure Labels

[0156] 10: Deep drawing test machine

[0157] 12: Mold

[0158] 14: Punch

[0159] 16: Anti-wrinkle components

[0160] W: Test plate

[0161] R: Radius of curvature of the corner of the punch

Claims

1. A copper alloy sheet having an alloy composition comprising one or both of Ni and Co in an amount ranging from 1.00% to 5.00% by mass, Si in an amount ranging from 0.20% to 1.50% by mass, and the balance being composed of Cu and unavoidable impurities. Tensile strength is above 550 MPa, and The area ratio of grains with GAM values ​​between 0.1° and 0.8° obtained from SEM-EBSD crystal orientation analysis data is between 30% and 90%.

2. The copper alloy sheet according to claim 1, wherein the work hardening index (n value) is in the range of 0.10 or higher and 0.20 or lower.

3. The copper alloy plate according to claim 1 or 2, wherein the average grain size obtained from the crystal orientation analysis data by SEM-EBSD method is in the range of 4 μm or more and 25 μm or less, and the standard deviation of the aforementioned average grain size is 6 μm or less.

4. The copper alloy sheet according to claim 1 or 2, wherein, The aforementioned alloy composition further contains at least one optional additive ingredient selected from the group consisting of Zn, Sn, Mg, Cr and Fe, in a total range of 0.10% by mass or more and 1.00% by mass. In cases where Cr is present, the Cr content is below 0.30% by mass. In the presence of Fe, the Fe content is below 0.30% by mass.

5. An electronic component formed using a copper alloy sheet according to any one of claims 1 to 4.

6. A forged product obtained by forging a copper alloy sheet as described in any one of claims 1 to 4.

7. A method for manufacturing a copper alloy sheet, comprising the method for manufacturing the copper alloy sheet according to any one of claims 1 to 4, and, For copper alloy materials with the same alloy composition as the aforementioned alloy composition, the following steps are performed sequentially: melting and casting [Step 1], reheating [Step 2], hot rolling [Step 3], first cold rolling [Step 4], first annealing [Step 5], second cold rolling [Step 6], second annealing [Step 7], third annealing [Step 8], third cold rolling [Step 9], and fourth annealing [Step 10]. In the aforementioned first annealing step [step 5], the temperature reached is set to a range of 800°C or higher and 1000°C or lower, and the holding time is set to a range of 5 seconds or higher and 30 seconds or lower. In the aforementioned second cold calendering step [step 6], the product of the processing rate [%] for each operation and the calendering roll diameter [mm] is set to 2000 [%·mm] or less. In the aforementioned third cold rolling step [step 9], the total processing rate is set to a range of 1% or more and 10% or less. In the aforementioned fourth annealing step [step 10], the temperature reached (T) is set to a range of 400°C or higher and 600°C or lower, while a tension (F (kgf / mm) is applied. 2 While annealing is being performed, the tension, expressed as a relationship with the aforementioned reached temperature (T(°C)), satisfies the inequality expressed by equation (I). −0.0015×T+1.20≤F≤−0.0015×T+1.80 Formula (I).

Citation Information

Patent Citations

  • Cu-Ni-Si BASED COPPER ALLOY SHEET EXCELLENT IN FATIGUE RESISTANCE AND SPRING PROPERTY AFTER BENDING WORKING, AND METHOD OF MANUFACTURING THE SAME

    JP2012136726A

  • Cu-ni-si copper alloy sheet with excellent deep drawability and process for producing same

    WO2012160726A1

  • Copper alloy sheet material and process for producing same

    CN103443309A

  • Copper alloy sheet, method for manufacturing same, electrical / electronic device heat radiation component, and sealed case

    CN111406122A